Stability analysis of an eco-epidemiological model consisting of a prey and two competing predators with SI-disease in prey and toxicant - Hincal, Evren; Mohammed, Shorsh; Kaymakamzade, Bilgen (Bulletin of the Karaganda University. Mathematics Series, 2020)
In the present paper, we study two eco-epidemiological models. The first one consists of a prey and twocompeting predators with SI-disease in prey species spreading by contacts between susceptible prey and infected prey. This model assumes linear functional response. The second model is the modification of the first one when the effect of toxicant is taken into account. In this paper, we examine the dynamical behavior of non-survival and free equilibrium points of our proposed model.